An enhanced characterization process for the elimination of very low level radioactive waste in particle accelerators. (December 2020) - Frosio, Thomas; Bertreix, Philippe; Magistris, Matteo; Menaa, Nabil; Michaud, Régis; Rimlinger, Maeva; Theis, Chris; Ulrici, Luisa; Zaffora, Biagio
Abstract: The elimination of very low level waste towards the French national repository requires their radiological characterization to estimate the radionuclide inventory and the associated activities within a waste package. Such characterization is performed by means of activation calculations and measurements. Two elimination projects have been identified at CERN, to dispose of bulk metallic waste and cables activated in the CERN accelerator complex. Based on the experience gained over the last 4 years, we develop a large scale elimination process to dispose of such types of activated equipment. A program for quality controls has therefore been developed through a novel software tool whose purpose is to compute the radiological data required by the repository for the acceptance of the waste as well as performing quality controls. Highlights: Enhanced characterization and classification process for radioactive waste in high energy particle accelerators. Software architecture for quality control and automatic waste radiological classification. Waste campaigns oriented processes.